Search for a light pseudoscalar Higgs boson produced in association with bottom quarks in pp collisions at $ \sqrt{s}=8 $ TeV - CMS collaboration (2235 authors) (2017)
A search for a light pseudoscalar Higgs boson (A) produced in association with bottom quarks and decaying into a muon pair is reported. The search uses 19.7 inverse femtobarns of proton-proton collisions at a center-of-mass energy of 8 TeV, collected by the CMS experiment. No signal is observed in the dimuon mass range from 25 to 60 GeV. Upper limits on the cross section times branching fraction, sigma(pp to b bbar A) B(A to mu mu), are set.